Resolusi Konflik Kelompok Kriminal Bersenjata Papua - Amanda, Muhammad Rasyiid; Pramono, Budi (Fakultas Syariah INSURI Ponorogo, 2023)
Papuan Armed Criminal Group has carried out various attacks on TNI-POLRI , Papuan civilians, and migrant civilians in recent years. Every act of terrorism that occurs disturbs the Papuan people who live or work there. There are many victims of the KKB attack in Papua, ranging from military personnel, teaching staff, medical personnel, then students who are studying in their school. The type of research that the author uses in writing this thesis is normative juridical research. This type of research is research that seeks solutions to legal issues that arise to provide prescriptions regarding what should be the issues raised. And using the Conceptual Approach, Statute Approach, and Comparative Approach. The Papuan armed criminal group does not match the characteristics and definition of terrorists, in which terrorists do not aim to establish their own country and seek their sovereignty through militia and diplomacy. The Papuan Armed Criminal Group aims to get international attention, hoping that the land of Papua can become a sovereign country. The Indonesian government's steps should be Belligerent preventive not limited to tackling terrorists. Resolving disputes with Papuan armed criminal groups by not committing acts that are categorized as international crimes is through the mechanism of Military Operations Other than War, Regional Expansion, and Infrastructure Development in the land of Papua. However, if the Armed Criminal Group is included in the Belligerent category, the Indonesian government can carry out Military Operations for War but must comply with the Laws of War or Mediation, Conciliation, and International Arbitration.